2017
DOI: 10.1177/1077699016687722
|View full text |Cite
|
Sign up to set email alerts
|

The Third-Person Effect of Online Advertising of Cosmetic Surgery: A Path Model for Predicting Restrictive Versus Corrective Actions

Abstract: Using survey data with a national representative of U.S. adult women, the current study tested both the perceptual and behavioral hypotheses for the third-person effect of online advertising of cosmetic surgery (OACS) in a theoretical process model. A strong third-person perception (TPP) was observed in assessing the influence of OACS. The results of a path analysis revealed that the self–other exposure gap and social undesirability were positive predictors of the TPP. TPP had a direct impact on support for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 75 publications
1
53
1
1
Order By: Relevance
“…At any level of attention (low, mean, high), frequent posting news increased preventive behavioral intention by reducing TPP; however, we could not find the significant mediating role of TPP in the relationship between viewing and preventive behavioral intention. Against other research results that only measured exposure to news (e.g., Lim, 2017;Wei et al, 2008), this study's findings imply that not all information-seeking activities on SNSs can be related to preventive behavioral intention through TPP. Given that SNSs are considered as participatory media, posting news as an active use is likely to be more powerful to exert risk perception rather than just viewing news on SNSs.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…At any level of attention (low, mean, high), frequent posting news increased preventive behavioral intention by reducing TPP; however, we could not find the significant mediating role of TPP in the relationship between viewing and preventive behavioral intention. Against other research results that only measured exposure to news (e.g., Lim, 2017;Wei et al, 2008), this study's findings imply that not all information-seeking activities on SNSs can be related to preventive behavioral intention through TPP. Given that SNSs are considered as participatory media, posting news as an active use is likely to be more powerful to exert risk perception rather than just viewing news on SNSs.…”
Section: Discussioncontrasting
confidence: 70%
“…They demonstrated that behavioral intention forms when an individual internalizes the TPP, meaning, it is because of that individuals' lower level of concern about bird flu for themselves that they did not tend to take actions to protect themselves. Moreover, Lim (2017) found that the other-self perceptual gaps in media exposure to online ads for cosmetic surgery lead to TPP, which in turn facilitates one's intention to support restrictions for cosmetic surgery ads. Though this study found a mediating role of TPP that leads to greater support for the regulation of online cosmetic surgery ads, scholars have found that such censorship of behavioral intention is caused by concern about the effects of media on society, rather than on oneself (i.e., Hoffner et al, 1999).…”
Section: Health Information-seeking On Sns and Third-person Perceptionmentioning
confidence: 99%
“…The term has been coined by research on presumed media influence. It describes actions that are reactive to (media) content perceived as harmful and that seek to influence the public sphere and counterbalance the negative influences of the content (Lim, 2017; Rojas, 2010). Recent empirical research on corrective action online includes sharing alternative opinions or information (Bernhard and Dohle, 2015; Golan and Lim, 2016) and engaging in online discussions to correct biases (Lim and Golan, 2011; Rojas, 2010).…”
Section: #Ichbinhier and Corrective Actionmentioning
confidence: 99%
“…Undesirability reflects the extent to which media messages are rejected by viewers (Jensen and Hurley, 2005). The magnitude of TPE perceptions is influenced by the undesirability of media messages (Lim, 2017). When a media message is perceived as undesirable, people tend to believe that they are less influenced by such messages and others are more likely to be influenced (Boyle et al, 2008).…”
Section: H4 Social Distance Positively Predicts Tpe Perceptions Of Imentioning
confidence: 99%